COMPARATIVE STUDY OF ARITHMETIC GEOMETRIC CURVE AND STATISTICAL STRAIGHT-LINE METHODS FOR HUMAN DEVELOPMENT INDEX PROJECTION - Harjanti, Diah Trismi; Enok Maryani; Muhammad Iqbal Apriliyana; Audi Cindra Arini (Universitas Airlangga, 2025)
The research compares the use of two projection methods, namely Arithmetic Geometric Curve (AGC) and Statistical Straight Line (SSL), in projecting the Human Development Index (HDI) in Sanggau Regency, West Kalimantan Province. In human development planning, choosing the right projection method is important. HDI is a complex indicator, with its growth not always linear, and that comparing the AGC method, which is more flexible to changing trends, with the SSL method, which is simpler but based on linear assumptions, will give an overview of the accuracy of the projection. This study investigates three main indicators of HDI, namely health, education, and a decent standard of living, through several main variables such as Life Expectancy, Expected Years of Schooling, Average Years of Schooling, and Per Capita Expenditure. The results between the two projections are significantly different. The projection of the AGC is more optimistic with a sharper growth trend, while the projection in the SSL method tends to be more stable and consistent. The AGC method indicates faster target achievement results, while the SSL method provides more accurate, realistic estimates. Thus, the HDI projection for Sanggau Regency shows that with the more aggressive AGC method, the HDI target of 70 can be achieved in 2025, while the SSL method leads to achieving the target in 2027. This study can provide the basis for regional development planning by considering the accuracy and stability of projections in achieving sustainable development.